Levels of Academic Burnout among Students of Psychology and Educational Sciences at the University of El Oued : An Exploratory Descriptive Study - falah, Yamina; Dahdi , Ismail; Lehelli , Mesbah; Rahma, Ghorab; Belgacem, Aouine; Younes, Ben hacine; Ahmed, Djelloul (Journal of Ecohumanism, 2026)
The present study addressed an academic psychological disorder experienced by a considerable category of university students due to the accumulation of several factors. This disorder is academic burnout. The present study aims to reveal the levels of academic burnout among students of Psychology and Educational Sciences at the University of El Oued, by adopting the descriptive exploratory method. In this study, a questionnaire was designed to measure academic burnout among students, consisting of 34 items. After calculating the validity and reliability of the questionnaire, we found that the questionnaire has a high level of validity and a high level of reliability, which indicates excellent reliability of the instrument. The questionnaire was also administered to a sample consisting of one hundred male and female students, selected through a stratified random method from the various specializations of Psychology and Educational Sciences at the University of El Oued. Several results were reached, the most important of which are: There are three levels of academic burnout among students of Psychology and Educational Sciences at the University of El Oued: Low academic burnout Moderate academic burnout High academic burnout Students who suffer from academic burnout need psychological assistance.